FORMULASI KRIM PENYEMBUH LUKA TERINFEKSI Staphylococcus aureus EKSTRAK DAUN TAPAK KUDA (Ipomoea pes-caprae (L.) Sweet PADA TIPE A/M - The, Falles Raintung; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2013)
ABSTRACT Beach Morning Glory is a plant that grew around the beach which has purple flower. Beach Morning Glory leaves contains chemical compounds such Flavonoids, Hydroquinone phenolic, alkaloids, and Tannins. Beach Morning Glory leaves has known as the medicine of acne and furunkulosis that caused by Staphylococcus aureus. The topical product is needed to heal the skin infection. The purpose of this research were to test about physical quality of cream based and Beach Morning Glory cream extract at the concentration between 2,5 %, 5 %, and 7,5%. The result shows the cream base and Beach Morning Glory cream with concentration of 2,5 %, 5 %, and 7,5 % fulfilled the Organoleptic and Homogenity test but was not fulfilled in the standart parameter of pH and spreadabillity. Keywords : Ipomoea pes-caprae (L.) Sweet, W/O Cream.